Brainstem encephalitis and the Miller Fisher syndrome. Issue 2 (February 1993) - Petty, R K; Duncan, R; Jamal, G A; Hadley, D; Kennedy, P G
Abstract : A case is described of a man with an acute onset areflexic ataxic syndrome with partial ophthalmoparesis and normal limb muscle power. There was evidence of both a peripheral neuropathy and a brainstem encephalitis. The patient made a full recovery and the interrelationship and nosology of brainstem encephalitis and the Miller Fisher syndrome are discussed.